Men With Hijab: Menetapkan Kejamakan Identitas Gender Cross-Hjaber di Media Sosial - Aly Mecca; Ahmad Fahrul Muchtar Affandi; Gumilar Pratama (JURNAL SOSIAL HUMANIORA (JSH), 2022)
Rejection of cross-hijaber is typical of societies with traditional gender ideologies in Indonesia. In Indonesia, cross-hijaber is stigmatized with criminal, psychiatric, and sexual disorders, as well as identity crises. This study examines how cross-hijaber displays his identity in the public and private spheres via social media, both communally and individually. Cross-hijaber social identity and cross-hijaber personal identity are examined in greater detail in this study. Using a virtual ethnographic method, the study examined cross-hijaber on a Facebook group. The results of the study reveal the diversity and complexity of cross-hijaber identities in social media interactions. The distinction between social and personal identities is no longer distinct because the two can exchange positions depending on context. When cross-hijabers begin to wear their hijab, their cisgender identities will be concealed. Even cross-hijaber identity is fluid based on the social context. Otherwise, when they become cisgender, the cross-hijaber identity will not be displayed.